Inkjet printed carbon nanotubes in short channel field effect transistors: influence of nanotube distortion and gate insulator interface modification. (25th August 2016) - Jang, Seonpil; Kim, Seohee; Geier, Michael L; Hersam, Mark C; Dodabalapur, Ananth
Abstract: We report on the effects of mechanical distortion and gate insulator-semiconductor interface modification on the electronic transport characteristics of inkjet printed short channel length single walled carbon nanotube (SWCNT) transistors with Al2 O3 top gate insulators. In these transistors, which are typically ambipolar, the average nanotube length is greater than the source-drain (S/D) spacing resulting in individual SWCNTs spanning the entire channel length. Mechanical distortion of the nanotubes due to bending near source and drain contacts when they are not recessed is found to suppress electron transport and transform the ambipolar transistors into p-type devices. Inclusion of printed interfacial polymer layers such as poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) between the SWCNTs and Al2 O3 also results in p-type doping and reductions in electron transport. We discuss mechanisms responsible for these effects.